Development of the SYAM (Synectic – Amtsal) Model in Islamic Religious Education Learning at SMPN 1 Margahayu - Abdillah Muflih; Fahmi Fazar; Faisal Fauzan Ilyasa; Rizal Permana; Syahidin (State Islamic Institute of Madura, 2024)
This study aims to develop and test the effectiveness of the SYAM (Synectic-Amtsal) Learning Model in improving student learning outcomes in Islamic Religious Education (PAI) subjects at the junior high school level. The SYAM model is designed by integrating the Synectic approach, which focuses on developing creativity and critical thinking through analogy, with the Amtsal method, which uses parables in the Qur'an to facilitate understanding of religious concepts. This study used a mixed methods approach with an exploratory sequential design, which involved qualitative analysis to design the model and quantitative tests to measure its effectiveness. The results showed that the implementation of the SYAM Model significantly improved students' understanding, as evidenced by the increase in mean scores from 79.35 in the pretest to 89.41 in the posttest based on paired sample t-test (p < 0.001) and Wilcoxon Signed Ranks Test (p < 0.001). This model not only helps students understand the material better but also improves critical thinking skills and internalization of religious values effectively. Nevertheless, this study has limitations on the number of samples and treatment duration, so it is recommended to conduct further research with wider coverage and longer duration. The results of this study make a significant contribution to the innovation of religion-based learning models that are interactive, relevant, and contextual to improve the quality of learning in schools.